PALIMPSESTS AND SYMBOLS: PRINCIPLES OF POETIC COMPOSITION IN JORGE DE LIMA’S INVENÇÃO DE ORFEU - Clarke, Margaret Anne (Revista de Estudos de Cultura, 2022)
The purpose of this essay is to resolve an apparent contradiction in the critical reception of the epic poem Invenção de Orfeu, by the preeminent Brazilian poet Jorge de Lima (1893 – 1953). The poet, according to his own account, had two principal aims in writing the poem: firstly, to effect a radical regeneration of poetry and poetics in order to renew religious and specifically Catholic values, in modern society, and secondly to modernise the classical and Renaissance epic genre, in its original Aristotelian sense, within the contexts of the twentieth century and the modern era. However, the critical scholarship concerning Invenção de Orfeu expresses the opposite view, that the work comprises a compendium of apparently unconnected and disassociated ideas, genres, textual fragments and poetic figures of all kinds, with no discernible sequence, and no thematic core. My aim, therefore, is to demonstrate the status of Invenção de Orfeu as a unified entity, with reference to Jorge de Lima’s single motive, repeatedly stated for composing his epic: to expound the principal tenets of the Catholic faith and “restore poetry in Christ”. I will use theory drawn from recent scholarship on theology and literature to illustrate the compositional structures underpinning the poem: firstly the one “root-metaphor” of the holy Trinity and Jesus Christ as the divine Logos, a concept on which all the verse in Invenção de Orfeu is based; secondly, the reintegration of “chains of memory” in order to re-establish a lineage of religious belief in a secularised world. Both of these principles, however, are realised through a poetics whose “invention” comprises a dynamic and multi-dimensional process of re-creation and re-composition of language by the poet. To illustrate, I will examine two particular features of Invenção de Orfeu, which, as I argue, transform Invenção de Orfeu into a thematic and stylistic unity. Firstly, the intertextuality inherent to the work: the appropriation and adaptation of classical and Renaissance epic texts interwoven in dense and intricate ways with Jorge de Lima’s own creation, to create a palimpsestic text. Secondly, the process of symbolisation, that is, the creation of symbols by the poet to generate a network of links, connections and relations within the language of the poem, which serve to render the text as one cohesive and integrated whole. Keywords: Brazil, religion, epic, poetry